Relación entre factores de riesgos y la prevalencia de enfermedades zoonóticas en la zona 3 Cotopaxi, Tungurahua, Chimborazo y Pastaza - Chuquimarca Chuquimarca, María Angélica (2022)
The objective of this research was to evaluate the relationship between risk factors and the prevalence of zoonotic diseases in zone 3 Cotopaxi, Tungurahua, Chimborazo, Pastaza, during the period 2014 - 2019 to determine the necessary control measures. 10,831 records taken directly from the MSP of the total number of people served in zone 3 were evaluated, of which 15 were positive for zoonotic diseases: 5 for Brucella, 8 for Leptospira and 2 for Mycobacterium, determining prevalence values of 0.046%, 0.073% and 0.018% respectively. The prevalence by provinces showed that brucellosis in Chimborazo was 0.018% higher than in the other provinces, in Cotopaxi it was determined as the highest prevalence for leptospirosis in the investigation with 0.027%, and finally Tungurahua as the one with the highest prevalence of tuberculosis with 0.018%. A survey was carried out on a sample of 371 people, which allowed establishing several important risk factors, such as male sex, age group between 26-54 years, families with a greater number of family members from 3 to 5, housewives, people dedicated to agricultural activity and students maintain the greatest risks by being exposed to zoonotic diseases. The survey allowed us to conclude that among the most important risk factors were the consumption of unpasteurized dairy products, contact with viscera, contaminated organs, animal body fluids, contact with rodents, lack of vaccination in domestic animals, lack of frequent review of animals to the veterinarian, lack of knowledge about zoonotic diseases, lack of daily cleaning, to which are added bites by dogs, cats and in some cases by bats.